2011
DOI: 10.1093/nar/gkr890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interaction with the hepatitis C virus mRNA reveals an alternative mode of RNA recognition by the human La protein

Abstract: Human La protein is an essential factor in the biology of both coding and non-coding RNAs. In the nucleus, La binds primarily to 3′ oligoU containing RNAs, while in the cytoplasm La interacts with an array of different mRNAs lacking a 3′ UUUOH trailer. An example of the latter is the binding of La to the IRES domain IV of the hepatitis C virus (HCV) RNA, which is associated with viral translation stimulation. By systematic biophysical investigations, we have found that La binds to domain IV using an RNA recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 55 publications
3
72
1
1
Order By: Relevance
“…The region C-terminal to the La module in genuine La and LARP7 proteins has been implicated in RNA chaperone and/ or folding functions. 13,[29][30][31] This part of the protein contains what we have identified as the xRRM2 (Fig. 1A).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The region C-terminal to the La module in genuine La and LARP7 proteins has been implicated in RNA chaperone and/ or folding functions. 13,[29][30][31] This part of the protein contains what we have identified as the xRRM2 (Fig. 1A).…”
mentioning
confidence: 91%
“…32,33 Recently, it was shown that the C-terminal half of hLa in concert with La module is required for HCV domain IV binding. 30 Both single-strand as well as structured duplex sequences were required for the association of hLa with RNA and the xRRM2 was shown to be critical for RNA binding, but the exact RNA sequence and structure requirements are still not clear. It appears that in genuine La proteins, the xRRM2 is important for RNA chaperoning activity; however, this function of xRRM2 in genuine La appears to be dependent on the La module.…”
mentioning
confidence: 99%
“…In this case, in addition to the LAM-RRM1 binding unit, a distal unconventional RRM2 is also involved (Martino et al 2012). Despite this difference, the LAM/RRM1 surfaces implicated in binding internal RNA regions are likely to overlap, at least partially, with the regions responsible for terminal 39UUU-OH recognition (Martino et al 2012). 4 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…This specific 39UUU-OH termini recognition is achieved through the synergic action of the LAM and the adjacent RRM1, that together form a uniquely tailored RNA-binding pocket, with several conserved amino acids in the LAM playing a crucial role in the interaction (Teplova et al 2006;KotikKogan et al 2008;Bayfield et al 2010). In the cytoplasm, most genuine La proteins can also modulate the translation of a subset of mRNAs by binding to internal, often structured, RNA regions (Holcik and Sonenberg 2005;Svitkin et al 2009;Martino et al 2012). In this case, in addition to the LAM-RRM1 binding unit, a distal unconventional RRM2 is also involved (Martino et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation